Making the transition to post-secondary education: Opportunities and challenges experienced by students with ASD in the Republic of Ireland - Shevlin, Michael; Mc Guckin, Conor (My University, 2017)
Internationally there are increasing numbers of young people on the ASD spectrum attending higher education. Early transition planning is essential and students with ASD often require support to articulate their post-school educational goals and actively participate in transition planning meetings. Services within higher education are primarily designed to provide academic supports however, non-academic supports may be an even more crucial factor in enabling successful transitions for young people on the ASD spectrum who often experience heightened anxiety within an unfamiliar environment. Within this paper, the results of a small-scale exploratory study of the transition experiences of six young people on the ASD spectrum to post-secondary education will be shared. There was limited evidence that transition planning had been initiated as a formal process for the six students. Accessing support in higher education proved to be a complex process for some students who required sustained input from parents to ensure that they would utilise the supports available. Encouraging the development of self-determination skills, a key predictor of success in higher education, needs to begin in secondary school. It is anticipated insights from this study can contribute to the development of an embedded infrastructure to support effective transitions for students with ASD to post-secondary education.
PUBLISHED
Keywords: Transition to post-secondary education; Students who experience ASD; Support services in higher education; Social interaction and curriculum; Inclusive Society; AUTISM; AUTISM SPECTRUM; Asperger Syndrome and Autism Spectrum Disorder; Autism; Autism; Autism; Autism; Autism; Autism Spectrum Disorder; EDUCATION; Autistic Spectrum disorders; Accessibility; Education